Evaluation of the indoor pressure distribution during building airtightness tests using the pulse and blower door methods. (15th May 2021) - Hsu, Yun-Sheng; Zheng, Xiaofeng; Cooper, Edward; Gillott, Mark; Wood, Christopher J.
Abstract: Building airtightness is a critical aspect for energy-efficient buildings as the energy performance of a building can be significantly reduced by poor airtightness. The Pulse technique has been regarded as a promising technology, measuring building airtightness at a low pressure of 4 Pa. However, due to the rapid dynamic nature of the test, a frequently raised question concerns the uniformity of the pressure distribution across the internal space of the test building during the air pulse release. In order to investigate this point, experimental work was conducted in a five-bedroom dwelling. All the tests were conducted at wind speeds less than 0.45 m/s to minimise the wind impact on the indoor pressure. The results show a pressure difference within the building during the Pulse test does exist, but considering the accuracy of differential pressure transducers, the deviation is not significant. In addition, a subtle variation is noted when the Pulse test was conducted at different locations on the ground floor, which may also be caused by variations in the environmental conditions. In terms of the airtightness measurement, a good overall agreement was found between the Pulse technique and the conventional blower door fan pressurisation method, which indirectly verified the uniformity of the indoor pressure distribution during both tests. Moreover, the error analysis demonstrated the validity of the measurement results for the two test methods in this study. Highlights: Pulse tests were performed in a large dwelling to represent a worst-case scenario. Both the Pulse and blower door tests showed a uniform indoor pressure distribution. The two methods have a good overall agreement on the airtightness measurement. The pulse release location had a minor impact on the airtightness measurement. The error analysis demonstrated the validity of the test results for both methods.